ECOSYSTEM APPROACH TO COMPETITIVENESS MANAGEMENT IN THE TERRITORIAL MARKET - SHTYK, Yulia; MYROSHNYCHENKO, Ganna; SEMENOVA, Darya; SOBOLEVA, Alina; SEMENOV, Stanislav (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article investigates the application of the ecosystem approach to competitiveness management in the territorial market in the conditions of a modern market economy. The purpose of the article is to substantiate the proposal for the introduction of an ecosystem approach to competitiveness management in the territorial market, as well as to identify factors that ensure its effectiveness. It is substantiated that effective competitiveness management requires taking into account the interaction between enterprises, scientific and educational institutions, government bodies and public organizations within the ecosystem. The use of the Simon matrix for analyzing the subjective and objective quality of goods and services as a strategic planning tool is proposed. The relationship between ecosystem services, socio-ecological potential and competitiveness of enterprises in the territorial market is revealed. In a market economy, it plays the role of a regulator of the price-quality ratio, promotes the emergence of new goods and technologies, and supports the dynamic development of industries. Despite the challenges, in particular, those associated with war and economic instability, territorial markets continue to develop thanks to automation, the introduction of autonomous technologies, and the latest innovative solutions. In the future, the ability to adapt to changes, introduce innovations, and ensure the efficiency of production processes will play a key role in the competitiveness of enterprises. Therefore, for development by an ecosystem approach, it is necessary to take into account the laws underlying the functioning of natural biogeocenoses. Losses in territorial markets are considered insignificant if they do not exceed the threshold of ecosystem sensitivity and its stability. Thus, it is necessary to propose that the ecosystem approach to managing competitiveness in the territorial market be understood as the ability of a business structure to mobilize a set of natural resources and ecosystem services and use them with maximum efficiency to obtain socio-economic benefits and ensure sustainable development.